Veteran peer suicide prevention: A community‐based peer prevention model. Issue 2 (20th April 2021) - Beehler, Sarah; LoFaro, Carl; Kreisel, Carlee; Dorsey Holliman, Brooke; Mohatt, Nathaniel V.
Abstract: Objective: The purpose of this study was to develop a conceptual model of community‐based veteran peer suicide prevention. Method: We conducted a qualitative study in which semi‐structured interviews were followed by three focus groups. Participants ( n  = 17) were chosen from community‐based organizations who had peers working on veteran suicide prevention; the sample included veteran peers, non‐peers, program managers, and community stakeholders. Interview data were analyzed thematically and inductively to identify key components and subcomponents of veteran peer suicide prevention. A draft model was shared with each focus group to elicit feedback and refine key concepts. Results: A conceptual model containing nine components and twenty‐six subcomponents was developed. Participants emphasized key organizational, relational, and practical elements needed to achieve positive outcomes. In addition, they described critical contextual and cultural factors that impacted veteran peers' ability to prevent suicide and promote overall wellness. Conclusions: Community‐based veteran peer efforts are a promising public health approach to preventing veteran suicide. Provided veteran peers are supported and fully allowed to contribute, these efforts can complement existing clinic‐based efforts. Future research on community‐based veteran peer suicide prevention should document a range of outcomes (e.g., clinical, wellness, financial) and allow for considerable flexibility in peer approaches.